Resistance evaluation to corrosion stainless steel used in vehicle exhaust - PrateS, Paula Emília de Souza; Prates, Glaucia Aparecida [UNESP]; Caraschi, José Claudio [UNESP]; Syed, Wasim Aluísio Prates (My University, 2016)
This study aims to assess the resistance to corrosion of stainless steels used in the manufacture of part of automotive exhaust systems, especially as regards ethanol fuel condensation in the rear silencer of light vehicles. One synthetic solution of ethanol fuel condensation has been formulated based on chemical analyses from specimens of natural solutions collected directly from the vehicle while running during its cold phase, that is, within the first 505 seconds. The assessment of resistance to corrosion of ferritic stainless steels AISI 439 and 409, as compared to the austenitic steel AISI 304, was carried out when in the presence of a synthetic solution of ethanol fuel condensation. The comparative analysis of the potentiodynamic polarization curves of the steels studied indicates that there is no difference in behavior concerning the corrosion of these steels. In addition, no identification of a potential of pitting within these curves could be observed. Upon implementation of Dip-Dry tests, it could be verified that the steels do in fact have a similar behavior in that they did not undergo corrosion, only oxidation. It could therefore be concluded that all the stainless steels studied can be recommended for use in the rear silencer of light vehicles and that the choice of a ferritic stainless steel would be the most economical among the three steels studied.
Keywords: Corrosion; Ethanol; Steel